A study protocol on the adaptation and validation of the Malay version of the Short Grit Scale (grit-s) on Malaysian university students - Abu Hasan, Hezne Ezaty; Abdul Khaiyom, Jamilah Hanum (Malaysian Psychiatric Association, 2019)
Introduction: Grit, an individual’s perseverance and passion for long-term goals, is a mouldable construct with contributions to success in many life domains. Grit’s cultivation in Malaysia can begin with a suitable instrument apt to measure it. The study aims to adapt and validate the Short Grit Scale (Grit-S), the Western-derived instrument to measure grit, as an economical justification to developing a new instrument, which is time consuming and costly.